Washington, D. C. Entwicklung und Gegenwartsbild der amerikanischen Hauptstadt - Ahnert, Frank (ERDKUNDE, 1958)
Washington holds a unique position among the capitals of the world. Planned as the seat of government, it has retained this primary function and, without the benefit of significant commercial or industrial activities, the population figure of its metropolitan area has far surpassed the one million mark and is already approcaching the second million. In 1790—91, after more than 7 years of discussion, the U. S. Congress decided to locate the new capital within a district 10 miles square (C = 100 sq. miles), excluded from the jurisdiction of the adjoining states Maryland and Virginia, immediately below the falls of the Potomac River, at the head of the tide. This location was to meet two conditions: centrality within the original 13 states, and accessibility from the sea. Thus Washington became one of the fall line cities. The geological boundary between the old metamorphic rocks of the Appalachian piedmont and the Cretaceous and younger sediments of the Atlantic coastal plain runs through the federal district (District of Columbia). In spite of its location near the coast, the climate of Washington is predominantly governed by continental air masses flowing in from interior parts of North America. Consequently the annual variation of temperature is rather high, and the comparatively small daily temperature range is additional evidence that the inflowing air masses are more important than local conditions of insolation and radiation. In summer rain is brought mainly by thunderstorms, in winter by warm fronts. Occasionally Washington lies in or near the path of hurricanes, their season being from June to October, and they constitute the only major maritime element in its climate and usually cause tremendous downpours. Snow occurs only for a few days, mostly in January or February. The street pattern of Washington was designed by Charles I’Enfant. It consists of a rectangular system of streets, on which another system of diagonally running avenues has been superimposed (cf. fig. 9). Many avenues converge on the President’s mansion, the White House, and on the Capitol; they are named after the states and territories of the Union, while the streets bear numbers and letters, arranged conveniently like a system of coordinates with the Capitol as point of origin. This city of I’Enfant was built on the lower Pleistocene terraces which make up the wide basin of confluence between the Potomac and Anacostia Rivers. Only after the Civil War was it expanded beyond to the higher terraces (above 600 ft.) and hills that surround the basin. Washington became the seat of government in 1800 and has been growing ever since. Its curve of population growth shows three periods of especially rapid increase: 1860—70 (Civil War), 1910—20 (World War I) and 1930—50 (economic depression and World War II). In these times of crisis, the government had to cope with new responsibilities and therefore had to expand its apparatus; the number of government employees was increased, and this led in turn to an increase in the number of people employed in socal service industries. Since 1920, with the advent of the automobile as a means of mass transportation, suburbs have been forming outside the Districts of Columbia, especially near the major roads. They have now merged into a broad suburban belt, and are still rapidly expanding into the rural areas of Maryland and Virginia. Territorially the area of the district was reduced by nearly one third in 1846, when the population on the right bank of the Potomac decided by plebiscite to return to Virginia. The population of Washington contains about 35 °/o negroes. Since the end of slavery, they have come to the city in search of work and settled mainly in the old residential sections from which the previous inhabitants were moving to the suburbs. Racial integration in schools was brought about in 1955, but the suburbs in Virginia still practise segregation. A considerable part of the inhabitants of Washington are young people (aged 20—30 years) who have come from other areas. There is also a disproportion of the sexes (891 men per 1,000 women) which is due to the predominance of clerical posts suited for women. In comparison with the average of all U. S. cities, the percentage figures of people employed in manufacturing and in public administration are reversed. In Washington 30.7 °/o of all employees work in public administration (U.S. city average 5.2 %>), while only 7.3 %> work in manufacturing (U.S. city average 29.4%); most of Washington’s manufacturing industries produce non-durable goods for consumption by the federal government and the local population. The federal government — a pure service institution at the national level — is by far the largest employer and here performs the function of the basic industry. All other occupations are of a secondary, type rendering services either to the government, or to Washington’s population, or to both. Politically, Washingtonians do not enjoy the same rights as other U. S. citizens. They are not represented in Congress, and their communal government is not administered by an elected mayor but by commissioners appointed by the President of the United Staates; Congress acts also as city parliament. The reasons are historical ones: the decision of Congress, in 1783, to create a federal district apart from other jurisdictions, and a crisis in the city’s finances in the 1870’s, for which Congress picked up the tab under the condition that Lenceforth all local affairs would be directed by Congress and the President. The people of Washington have repeatedly tried to obtain home rule and representation in Congress, but as yet without success. Land use in the District of Columbia follows a rather well-defined functional pattern. Its elements are the government buildings and other public and semi-public land holdings, the business districts, land occupied by railways and industry, residential areas and parks. The overall pattern of functional units resembles concentric belts (cf. figs. 16 and 17). In the centre lies the government district, on both sides of the broad Mall from the Capitol westward to the Potomac. Most of the federal departments and other establishments are located there. North of it, but still part of the functional centre, stretches the central business district, mainly along F and G streets, N. W. This core, shared by government and business, is surrounded in the north, east and south by the old residential belt, the outer limits of which closely conform to the boundaries of I’Enfant’s street plan. Its basic elements are old terrace houses, largely occupied by negroes. Scattered throughout are newer apartment buildings which reach their highest concentration near the northwestern edge of the central area; many government and business employees live here. Business establishments extend ribbonlike through this belt along the major streets. Their shops, restaurants and filling stations serve the neighbourhood as well as through-traffic. The area outside this old residential zone forms a second belt, which is, however, much more heterogeneous. Partly for physical, partly for historical reasons it can be subdivided into five different sectors: Sector I lies west of the deeply incised valley of Rock Creek. Its inner parts contain a multitude of land uses, public and semi-public property intermingled with different types of residential buildings, but farther out it gradually leads into a rather homogeneous district of single family houses. Sector II is occupied by the north-south valley of Rock Creek; with its steep slopes originally an obstacle to settlements and traffic, it is now a wooded park with playgrounds, golf courses, picnic sites and the Washington Zoo. Sector III, along the eastern edge of Rock Creek Park, has the highest population density within the outer belt. It is the only sector dominated by terrace houses, though more modern types than those in the old residential belt, and with a greater proportion of white inhabitants. Here again the blocks of terrace houses are penetrated by ribbon-like business sections along main streets. Sector IV adjoins sector III to the east and is made up predominantly of public and semi-public properties like the U. S. Soldiers’ Home, the Catholic University, the McMillan Reservoir, and cemeteries situated on land which was acquired before urban development reached this area; therefore little land was later available for residential purposes. Consequently, this sector is very little populated. Sector V, between sector IV and the Anacostia River, may be divided further into a western part (Va), where single family dwellings predominate, and an eastern part (Vb) composed of railway yards, small industries and warehouses, and public land, e. g. National Arboretum, Training School for Boys. Sector VI, east of the Anacostia, is characterized by an irregular, patchwork land use pattern. All residential house types occur here, intermingled with parks and other public land, shopping districts, etc. The suburbs outside of the District of Columbia are dominated by modern single family houses, with apartment districts in the vicinity of the main through roads. Commercial development is limited to shopping centres, agglomerations of shops with large parking areas. In contrast to other American cities, land use in Washington is characterized by its great proportion of public land and parks, and the small area devoted to industrial and commercial uses. Further physiognomic differences are the prevalence of trees throughout the city, lining most streets and squares and thus giving the whole city a park-like appearance, and the restricted heights of private buildings. Zoning laws keep building heights at 110 ft. and under, in order to preserve the architectural eminence of the Capitol dome and the George Washington Monument. This absence of skyscrapers also distinguishes Washington from other American cities of similar size. With regard to communications, the fall line location has long creased to be of much importance. Washington is still a minor port, but half of its annual receipts consists of sand and gravel dredged from the Potomac; the other half is made up of petrol, fuel oil, newsprint, fish, and other goods for consumption within the metropolitan area. Hardly any cargo leaves Washington by water. The freight traffic by rail and road through Washington is rather heavy due to the bridges which permit easy crossing of the Potomac River here at the upper end of its estuary. A large railway yard on the Virginia bank of the Potomac signifies this focal transport location. Passenger traffic is divided between rail, air and road; railways and aeroplanes serving mainly long-distance traffic while the motor vehicles (including buses) are used both for longdistance travel and daily commuting. Within the metropolitan area tram lines are still in use. Traffic congestion is remarkable, particularly during rush hours. Future planning in this fast-growing city will have to be very much concerned with traffic problems. The airport is already working to capacity, and construction of a second airport is now being discussed in Congress. Further decentralization of government buildings, together with the construction of limited access roads, will help to relieve the increasing traffic congestion, especially in the zentral parts of the city. Another problem is that of slum clearance in the terrace house sections of the old residential belt. Several blocks have already been pulled down, and are to be replaced by modern office buildings and apartment houses. But the main growth takes place in the suburbs. Particularly in Maryland the suburbs of Washington extend for many miles northward along main roads; they will eventually merge with the suburban tentacles which stretch from Baltimore southward, thus linking Washington with that long ribbon of conurbation which follows the Atlantic coast all the way to southern New England.